Sex-specific prediction of hypothalamic-pituitary-adrenal axis activity by pituitary volume during adolescence: a longitudinal study from 12 to 17 years of age - Kaess, Michael; Simmons, Julian G.; Whittle, Sarah; Jovev, Martina; Chanen, Andrew M.; Yücel, Murat; Pantelis, Christos; Allen, Nicholas B. (Psychoneuroendocrinology, 2013)
Objective - To investigate the longitudinal relationship between pituitary gland volume (PGV) and parameters of hypothalamic-pituitary-adrenal axis (HPAA) functioning during adolescence. - Methods - Participants were 49 adolescents (19 girls and 30 boys) selected from a larger longitudinal, population-based study of adolescent development. Assessments were conducted at three time points (S1, S2 and S3). MRI sessions were at S1 (age: M=12.62, SD=0.45 years) and S3 (M=16.48, SD=0.53 years) and multiple assessments of salivary cortisol were undertaken at S2 (M=15.51, SD=0.35 years). PGV was measured via previously validated manual tracing methods, and the cortisol awakening response (CAR) and diurnal slope (DSL) were used as indices of HPAA functioning. - Results - A significant sex-linked interaction was found for PGV at S1 predicting both CAR (p=0.025) and DSL (p=0.009) at S2. Specifically, PGV at S1 significantly predicted CAR (p=0.033) and DSL (p=0.010) in boys only, with no significant results found for girls. Neither CAR nor DSL at S2 predicted growth of PGV from S1 to S3. - Conclusions - PGV in early adolescence predicted HPAA functioning in mid-adolescent boys but not in girls. The results suggest a significant influence of sex-specific development on the relationship between PGV and HPAA activity and reactivity. The findings have potential implications for understanding and interpreting sex-linked and stress related clinical disorders that emerge during mid-to-late adolescence.